Transition, Action, Details; Helping the Students to Write Easily - Abdul Aziz Rifaat; Nyayu Yayu Suryani (Institut Agama Islam Negeri Palopo, 2022)
Writing means implementing all parts of its stages. Once the writer misses one of its stages, the product of the writing should not be as expected. The TAD is one of the writing strategies to help the writer easier to write especially in the recount text. The objective of this study was to find out the significant difference in writing achievement before and after the students was taught by using The TAD strategy. The pre-experimental design was used in this study. The population and the sample of this study was all 3rd semester bachelor’s degree of nursing students at the institute of health science Siti Khadijah Palembang in the academic year 2020/2021. The total number of the sample was 30 students. The total sampling technique was used to select the sample in this study. The writing test was used as an instrument to collect the data in this study. The test was given before the treatment as a pretest and after the treatment as a posttest. The result of the study showed that there was a significant difference before and after the students were taught by using the TAD strategy.